Facial Reanimation in the Seventh and Eighth Decades of Life. Issue 5 (May 2018) - Hembd, Austin; Harrison, Bridget; Rocha, Cynthia Souza Martins; Rocha, Franklin de Souza; Chamseddin, Khalil; Labbé, Daniel; Cárdenas-Mejía, Alexander; Rozen, Shai M.
Abstract : Background: Treatment of facial paralysis in the older population is often relegated to static rather than dynamic reanimation for fear of poor outcomes. This pervasive approach lacks physiologic foundation and is not evidence based. Thus, the authors present an extensive literature review demonstrating weak evidence supporting this misguided concept, followed by detailed outcomes from three centers of the largest reported series to date of patients older than 60 years after reanimation performed using three techniques—lengthening temporalis myoplasty, free functional muscle, and nerve transfers. Methods: A PubMed search spanning over 40 years identified all reports on reanimation in patients older than 60 years. In addition, detailed demographics, surgical techniques, and outcomes of 30 patients older than 60 years were analyzed. Results: Of 629 articles, only 45 patients were identified, described in case reports or small series, lacking details or consistent long-term follow-up. In the clinical series, average age, preoperative House-Brackmann score, and comorbidities were similar among the groups. Highest excursion was observed in the free functional muscle group, followed by nerve transfer and temporalis myoplasty, averaging 10.4, 6.8, and 3.1 mm, respectively. The most notable philtral deviation correction was in the lengthening temporalis myoplasty group, followed by the free muscle and nerve transfer groups, averaging 5.6, 2.2, and 1.13 mm, respectively. Complication rates were highest in the free functional muscle group. Conclusions: Facial palsy patients should not be denied dynamic restoration based on age alone. Although surgical technique may vary based on duration of palsy, surgeon experience, and preference, with each presenting advantages and disadvantages, dynamic restoration is feasible regardless of age. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV. Abstract : Supplemental Digital Content is available in the text.